Analysis of Historical Trends and Recent Elimination of Malaria from Sri Lanka and Its Applicability for Malaria Control in Other Countries - Wijesundere, Dilkushi Anula; Ramasamy, Ranjan (Frontiers in Public Health, 2017)
Sri Lanka is a tropical island located South of India in the Indian Ocean. Malaria has been prevalent in the island for centuries but the country succeeded in eliminating the disease in 2012. The reasons underlying the past endemicity of malaria and malaria elimination in Sri Lanka in 2012 are analyzed. There is evidence that malaria might have been first introduced in the 13th century into a dry zone area with extensive irrigation works. Regular widespread epidemics of the disease have been documented in the 20th century. The island nature of Sri Lanka, generally low transmission rates, widespread and accessible government hospitals and clinics that provide free and readily available diagnosis and treatment for malaria, adequate financial support and commitment to the Anti-Malaria Campaign (AMC), national and decentralized malaria control efforts sustained over a long period by dedicated and competent AMC staff, and the absence of zoonotic malaria are recognized to have been some of the key responsible factors for the elimination of malaria in Sri Lanka. These factors are analyzed in the context of their relevance to the present malaria situation and ongoing elimination efforts in other countries.